The Eternal Axis of the Kaaba as Cosmic Nexus and Interfaith Catalyst - Maspul, Kurniawan Arif (Pubmedia Social Sciences and Humanities, 2025)
The Kaaba, an ancient cubic structure in Makkah, Saudi Arabia, stands as a timeless symbol of spiritual centrality, cosmic order, and human unity. More than a physical edifice, it functions as the axis mundi, a metaphysical anchor connecting heaven and earth, a focal point for the collective consciousness of 1.9 billion Muslims, and a sacred site revered across Abrahamic traditions. This study explores the Kaaba’s multidimensional significance, integrating Islamic theology, sacred geometry, neuroscience, and astrophysics to reveal its deeper spiritual, psychological, and scientific dimensions. The Kaaba’s geometric precision aligns with sacred proportions such as the golden ratio (1.618), found in natural formations, galaxies, and DNA helices, suggesting an underlying cosmic design (Livio, 2008). Neuroscientific studies demonstrate that rituals like tawaf (circumambulation of the Kaaba) induce theta brain wave activity, fostering deep meditation, emotional resilience, and neural synchronization (Newberg & Waldman, 2010). From an interfaith perspective, the Kaaba shares symbolic parallels with the Temple Mount in Judaism and the Church of the Holy Sepulchre in Christianity, reinforcing the universal yearning for a divine connection. n an era of fragmentation, the Kaaba emerges as a beacon of unity, bridging faith, science, and civilization itself. Its enduring legacy, both spiritual and scientific, calls for a renewed appreciation of sacred knowledge—not as an artifact of the past but as a guiding principle for global harmony, interfaith dialogue, and the rediscovery of our interconnected existence.